An innovative thermal protective clothing system for firefighters - Gilda Santos; Rita Marques; Francisca Marques; João Ribeiro; André Fonseca; João M. Miranda; João B. L. M. Campos; Soraia F. Neves (Communications in Development and Assembling of Textile Products)
Nowadays, despite the evolution of personal protective equipment (PPE), the number of firefighters injured and burned during fire extinguishing operations is still very high, leading in some cases to loss of life. Therefore, the research and development of new solutions to minimize firefighters’ heat load and skin burns, with consecutive improvements of commercial firefighters’ suits, is of extreme importance. The integration of phase change materials (PCMs) in a protective clothing system has been used to significantly reduce the incoming heat flux from the fire environment. This study consists in the development of a protective clothing system composed by a vest, specially designed to protect the torso (back, chest and abdomen) with a layer of PCM pouches, to be worn over a fire-resistant jacket – selection and design based on numerical models’ predictions. Therefore, several mockups were made, varying the number of PCM pouches and their distribution in the vest, allowing the creation of air ducts to increase the breathability of the vest. The most promising solutions are being evaluated in a real controlled environment, at a Portuguese National School of Firefighters (ENB) simulation site, using a fire manikin and thermocouples to monitor vest temperature during heat and flame exposure, and consequently to verify PCMs influence in heat protection. Results regarding the development of a PCM vest will be presented, focusing on the integration of PCM pouches and the thermal performance of the most promising solutions.